2022
DOI: 10.1007/s00404-022-06436-0
|View full text |Cite
|
Sign up to set email alerts
|

Intra-cavitary fluid resulted from caesarean section but not isthmocele compromised clinical pregnancy after IVF/ICSI treatment

Abstract: The aim of this study was to explore whether the presence of intra-cavitary fluid (ICF) influences the pregnancy outcomes of patients with caesarean section (CS) in embryo transfer cycles. A total of 8494 transferred cycles of 4924 women were enrolled in this retrospective study and separated into three subgroups by previous delivery method and the presence of intra-cavity fluid, a caesarean group with ICF (CS-ICF, n = 649), a caesarean group without ICF (CS-noICF, n = 3207), and the remaining 4638 cycles with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In addition, the co-occurrence network of fungal communities and the stability of the bacterial-fungal cross-domain network in the CSD group are poorer than those in the CON group, indicating that the cervical microbiota stability is disrupted in CSD, resulting in local microbial-immune imbalance. A previous study confirmed that persistent exudation in CSD is a crucial factor affecting embryo implantation [7]. Several studies have shown that microbial dysbiosis can affect local immune balance and cause inflammation [36, 37].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, the co-occurrence network of fungal communities and the stability of the bacterial-fungal cross-domain network in the CSD group are poorer than those in the CON group, indicating that the cervical microbiota stability is disrupted in CSD, resulting in local microbial-immune imbalance. A previous study confirmed that persistent exudation in CSD is a crucial factor affecting embryo implantation [7]. Several studies have shown that microbial dysbiosis can affect local immune balance and cause inflammation [36, 37].…”
Section: Discussionmentioning
confidence: 69%
“…A niche can reduce the chances of embryo implantation and increase the likelihood of spontaneous miscarriages if the implantation occurs close to or in the CSD [6]. Our previous studies have shown that the persistent effusion of CSD is a key cause of failed embryo implantation [7].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, patients with cesarean section history were more likely to have persistent ECF compared with those without. The impaired local mucosal function of the uterus in women who underwent cesarean deliveries can lead to the occurrence of endometrial inflammation and impaired decidualization [18] . In addition, cesarean section scar will destroy the continuity of local uterine muscle fibers, and interfere with uterine contraction, which affects the discharge of uterine fluid and leads to uterine fluid accumulation [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The universal primers 341F (5′-CCTACGGGNGGCWGCAG-3′) and 805R (5′-GACTACHVGGGTATCTAATCC-3′) were used for 16s rRNA genes sequencing ( 30 ). DNA extraction and library construction were as described in our previous study ( 7 ). In short, according to the manufacturer's instructions, we used Magpure Soil DNA LQ kit (MAGEN, D6356-02) to conduct a total DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The spontaneous pregnancy rate in CS women has decreased by 15%, and even with assisted reproductive technology, the embryo implantation and live birth rates are significantly lower ( 6 ). Our previous research revealed that persistent effusion is the major factor affecting fecundity in CSD women ( 7 ).…”
Section: Introductionmentioning
confidence: 99%